Prolonged fecal shedding of replication-competent virus, lasting immune activation, and intestinal inflammation in a rhesus macaque after experimental SARS-CoV-2 infection - Böszörményi, Kinga P.; Stammes, Marieke A.; Fagrouch, Zahra; Acar, Fidel; Niphuis, Henk; Kayere, Gwendoline Kiemenyi; Meijer, Lisette; Snijder, Eric J.; van der Hoek, Lia; Berkhout, Ben; Bogers, Willy M.; van den Brand, Judith M. A.; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Infection of an adult rhesus macaque with SARS-CoV-2 led to viral RNAemia in nose, throat, and lungs. The animal also presented extended fecal shedding of viral genomic and subgenomic messenger RNA and replication-competent virus for more than 3 weeks after infection. Positron emission tomography revealed increased intestinal glucose metabolism which was histologically related to inflammation of the ileum. These findings highlight the potential of the virus to cause gastrointestinal infections in macaques like this is also regularly observed in COVID-19 patients and substantiates the probability of virus transmission via the fecal-oral route. This study further adds the importance of nonhuman primates as a valuable animal model to study SARS-CoV-2 infection in humans.